Aspek Legal Spirit Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga - Elias Zadrach Leasa (SASI, 2018)
Families are places where everyone in the family feels safe and comfortable from acts o violence, but in reality violence also accurs whitin the family. The enactment of Law No. 23 of 2004 on the abolition of domestic violence (hereinafter referred to as the Law of Domestic Violence) aims to prevent all forms of domestic violence, protect domestic violence victims, prosecute domestic violence perpetrators, and maintain wholeness harmonious and prosperous households. In handling it is sometimes resolved peacefully. This raises the question of whether the Law on Elimination of Domestic Violence has guaranteed the settlement of Domestic Violence according to its objectives? All forms of violence against women and children constitute a violation of human rights, so it is necessary to be protected by their dignity and dignity and guaranteed their right to life in accordance with their nature and nature without discrimination. The Criminal Act contained in Article 5 of the Act states that prohibited violence is physical violence, psychological violence, sexual violence, or neglect of the household. Many cases of domestic violence are reported but not a few are repealed by the victim for various reasons, such as still loving the perpetrator, and the perpetrator is the breadwinner in the household. The resolution of cases of domestic violence is also up to the court's decision, but this certainly brings the consequences of the objective of the Law on Elimination of Domestic Violence. Despite all forms of prevention of domestic violence, protecting the victim, prosecuting the perpetrator is reached but if the case is passed on to the court decision whether the goal of maintaining a harmonious and prosperous household unity can be achieved. The resolution of domestic violence requires the wisdom of the Law Enforcers (Police, Prosecutors, Judges).